What effects could global value chain and digital infrastructure development policies have on poverty and inequality after COVID-19? - Ximena V. Del Carpio; José Cuesta; Maurice Kugler; Gustavo Hernández; Gabriel Piraquive (Journal of Risk and Financial Management, 2022)
It is clear that in the transition out of the COVID-19 crisis in Colombia there will be great need for formal job creation. One source that has been widely discussed in policy circles is strengthening linkages of Colombian firms with Global Value Chains (GVCs). Another source that has received recent attention, and deservedly so, is digital infrastructure development (DID)-which can boost telework and virtual human capital accumulation. Reduction in poverty and inequality through more and better formal employment is an important aspect of a jobs and economic transformation (JET) agenda. In this paper, we explore-through a computable general equilibrium model (CGE) and a microsimulation framework-to what extent reforms of the type envisioned in the JET agenda and which could generate GVC linkages, as well as through DID, for Colombia, and we project their impact on poverty and inequality up to 2030. Our findings show limited impact of the three types of policy changes considered for GVCs-namely (i) fall in barriers for seamless business logistics, (ii) reductions in tariffs, and (iii) lower barriers to foreign direct investment (FDI). The impact of DID on inequality is also moot. There is however a modest impact on poverty reduction in the combined policy of digital infrastructure with a boost in skilled labor. This finding can be linked to different factors. First, there are relatively few direct jobs created to benefit households with low levels of human capital. Second, there might be indirect job creation through backward linkages to local suppliers by firms linked to GVCs, but this effect would be a general equilibrium effect that our CGE model with a partial equilibrium microsimulation distributional module does not fully capture. Third, the positioning of Colombian firms to latch onto GVCs, and also generate demand for local intermediate inputs and services, is not optimal. Fourth, DID may generate more general labor market opportunities through telework and virtual learning expansions but could also induce larger wage gaps as the skill premium rises so that the net effect on inequality is ambiguous.
Keywords: F14; J23; J24; J63; L86; O15; O33; 330; COVID-19 pandemic; aggregate supply and demand shocks; income fall; poverty; inequality; JET; GVCs; productivity; formal employment; wages; CGE; microsimulations